Effect of tungsten doping on perpendicular magnetic anisotropy and its voltage effect in single crystal Fe/MgO(0 0 1) interfaces. (9th January 2020) - Iida, Yuki; Xiang, Qingyi; Okabayashi, Jun; Scheike, Thomas; Sukegawa, Hiroaki; Mitani, Seiji
Abstract: Heavy metal elements with strong spin–orbit coupling generally play an important role for perpendicular magnetic anisotropy (PMA) in magnetic heterostructures. We examined interface PMA and related properties in single crystal Fe/MgO(0 0 1) heterostructures in which a very thin W interface layer was nominally inserted as doping. The PMA energy density was reduced with increasing the W layer thickness, in contrast to the results in a similar study using poly-crystal FeB/MgO heterostructures (Nozaki et al 2018 APL Mater . 6 026101), suggesting that the detailed mechanisms of PMA are different between single crystal Fe/MgO and poly-crystal FeB/MgO. X-ray magnetic circular dichroism measurements revealed that anisotropy in the Fe orbital magnetic moments decreased with the PMA energy density, i.e. the PMA observed was interpreted in the framework of Bruno's model (Bruno 1989 Phys. Rev . B 39 R865). The coefficient of the voltage effect of PMA arising in the Fe/MgO heterostructure with 0.05 nm thick W interface insertion was determined to be 190 fJ Vm −1, showing a small quantity of reduction as well as the PMA. This study gives an insight into the role of heavy metal elements in the PMA for single crystal Fe/MgO heterostructures.